THE ROLE OF COPYRIGHT LEGAL PROTECTION IN ENSURING LEGAL CERTAINTY FOR BOOK PRINTING BUSINESSES IN INDONESIA - Samudra, Hari; Hasibuan , Marwah Saputri; Bahri, Rafli Abdul; Musoddih, Sit Syaiyah (LEX SOCIETAS: Journal of Law and Public Administration, 2025)
This study examines the role of legal protection of copyright in ensuring legal certainty for book printing businesses in Indonesia. Although Law No. 28 of 2014 on copyright provides a fairly clear legal framework, its implementation in practice still faces various obstacles, such as low understanding among business actors, weak socialization, and complicated administrative procedures. Through a qualitative approach using normative legal and sociological legal methods, this study finds that copyright protection has not yet fully provided a sense of security and legal certainty for the printing industry, particularly for small and medium- sized businesses. Therefore, there is a need to strengthen legal education, simplify legalization processes, and develop inter-institutional strategies for the legitimate, sustainable, and competitive development of the industry in the era of an intellectual property-based economy.